Vitamin A Impairs the Reprogramming of Tregs into IL-17-Producing Cells during Intestinal Inflammation. (25th October 2015) - Tejón, Gabriela; Manríquez, Valeria; De Calisto, Jaime; Flores-Santibáñez, Felipe; Hidalgo, Yessia; Crisóstomo, Natalia; Fernández, Dominique; Sauma, Daniela; Mora, J. Rodrigo; Bono, María R.; Rosemblatt, Mario
Abstract : Maintaining the identity of Foxp3 + regulatory T cells (Tregs) is critical for controlling immune responses in the gut, where an imbalance between Tregs and T effector cells has been linked to inflammatory bowel disease. Accumulating evidence suggests that Tregs can convert into Th17 cells and acquire an inflammatory phenotype. In this study, we used an adoptive transfer model of Ag-specific T cells to study the contribution of different factors to the reprogramming of in vitro -generated Treg cells (iTreg) into IL-17-producing cells in a mouse model of gut inflammation in vivo . Our results show that intestinal inflammation induces the reprogramming of iTreg cells into IL-17-producing cells and that vitamin A restrains reprogramming in the gut. We also demonstrate that the presence of IL-2 during the in vitro generation of iTreg cells confers resistance to Th17 conversion but that IL-2 and retinoic acid (RA) cooperate to maintain Foxp3 expression following stimulation under Th17-polarizing conditions. Additionally, although IL-2 and RA differentially regulate the expression of different Treg cell suppressive markers, Treg cells generated under different polarizing conditions present similar suppressive capacity.